Imam Nawawi's Thought On Teacher Personality Competencies And Their Relevance To National Education Standards - Toro Yudistiro; Nur Hadi (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The education system expects teachers to be more competent as educators. This means that the teacher must be proficient and professional. This study aims to find the concept of educator personality from the thoughts of al-Imām an-Nawawī in his book At-Tibyān Fī 'Ādāb Hamalati Al-Qur'ān and also its relevance to the National Education Standards set by the Indonesian Ministry of Education. The type of research that researchers use is qualitative research with a literature review approach by describing Imam Nawawi's thoughts and discussing their relevance to teachers and National Education Standards. The primary data source is from the book At-Tibyān written by Al-Imām Al-Nawawi. From the analysis that has been carried out, it is found that the concept of educator personality from Imam Nawawi's thought, namely: (1) Educators should carry out their responsibilities sincerely with the sole intention of expecting the pleasure of Allah SWT. (2) Educators do not intend to obtain worldly pleasures. (3) Educators must always be careful and thorough. (4) Educators should adorn themselves with commendable qualities and good morals. (5) Students must be treated well by educators. (6) Educators should advise their students. (7) Educators must be gentle and humble 8) Students must be taught to behave in a way that is approved by Allah SWT by their teacher from time to time. (9) If there are many students, the teacher should give priority to the first student's turn and so on. (11) The teacher may not teach by coming to the student's place.  Keywords: Imam Nawawi's Thoughts, Educator Personality, Professional Teacher